2012
DOI: 10.7205/milmed-d-12-00180
|View full text |Cite
|
Sign up to set email alerts
|

Spice, Bath Salts, and the U.S. Military: The Emergence of Synthetic Cannabinoid Receptor Agonists and Cathinones in the U.S. Armed Forces

Abstract: Designer drugs are synthetic compounds that contain modified molecular structures of illegal or controlled substances. They are produced clandestinely with the intent to elicit effects similar to controlled substances while circumventing existing drug laws. Two classes of designer drugs that have risen to recent prominence are "spice," synthetic cannabinoid receptor agonists that mimic the effect of tetrahydrocannabinol, the active ingredient in cannabis, and "bath salts," synthetic cathinones, stimulants stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 38 publications
0
35
0
1
Order By: Relevance
“…On 21 October 2011 the US Drug Enforcement Agency placed a temporary federal ban on a number of bath salt compounds [1]. Reaching a high of 744 calls in June 2011, the American Association of Poison Control Centers (AAPCC) reported a decline in national PCC calls beginning in July 2011 (678) and decreasing markedly in October 2011 (400).…”
Section: The Effect Of Legal Bans On Poison Control Center Contacts Rmentioning
confidence: 99%
See 1 more Smart Citation
“…On 21 October 2011 the US Drug Enforcement Agency placed a temporary federal ban on a number of bath salt compounds [1]. Reaching a high of 744 calls in June 2011, the American Association of Poison Control Centers (AAPCC) reported a decline in national PCC calls beginning in July 2011 (678) and decreasing markedly in October 2011 (400).…”
Section: The Effect Of Legal Bans On Poison Control Center Contacts Rmentioning
confidence: 99%
“…Synthetic cathinones, known more commonly as 'bath salts' in the United States, are a class of psychostimulants differing structurally from amphetamines by only an additional ketone [1]. On 21 October 2011 the US Drug Enforcement Agency placed a temporary federal ban on a number of bath salt compounds [1].…”
Section: The Effect Of Legal Bans On Poison Control Center Contacts Rmentioning
confidence: 99%
“…The major users of SCs have been suggested to be populations wishing to avoid drug detection such as parolees, students and military staff due to the inability of the drug to be detected through the standard urine drug screening [8]. Another hypothesis has been proposed that SC's may be used as an adulterant to unsuspecting consumers under the guise of marijuana, due to the relatively low price of about $6-10 USD per gram [9].…”
Section: Discussionmentioning
confidence: 99%
“…In this age group, ever SC use was first reported to be around 10% (e.g., Barratt et al, 2013;Forrester, Kleinschmidt, Schwarz, & Young, 2012;Gunderson, Haughey, AitDaoud, Joshi, & Hart, 2014;Hu, Primack, Barnett, & Cook, 2011;Vandrey et al, 2012), but the recently published results of a self-reported study, including almost 15,000 participants from different countries, revealed lifetime use to be more prevalent: 16.8% (Winstock & Barratt, 2013). Accumulating evidence demonstrates the increasing popularity of SCs amongst soldiers (Bebarta, Ramirez, & Varney, 2012;Loeffler, Hurst, Penn, & Yung, 2012) and athletes (Heltsley et al, 2012;M€ oller et al, 2011).…”
Section: Users Routes Of Administration Dosagesmentioning
confidence: 93%